A Framework for the Wellness Destination Image of Malaysia - Liew, Fifi Ee En (Curtin University, 2024)
The thesis presents a qualitative study of the wellness destination image of Malaysia and the destination attributes shaping it. A framework for wellness destination image is developed in the context of Malaysia, supporting the Sustainable Development Goal 3 (Good Health and Well-Being) and the National Tourism Policy 2020-2030.